Penyuluhan Urgensi Tera Ukur/Sertifikasi Timbangan di Pasar Kahayan Kota Palangka Raya - Rahmad Kurniawan; Jefry Tarantang; Wahyu Akbar; Ahmad Dakhoir; Novi Angga Safitri (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
The target of this outreach activity is business actors in Kahayan Market who use weighing tools in their sales. The devotees carry out various efforts aimed at increasing protection for consumers and maintaining the quality of circulating goods and services that are good for the community or consumers. The devotees carry out various efforts aimed at increasing protection for consumers and maintaining the quality of circulating goods and services that are good for the community or consumers.